2019
DOI: 10.1177/2516608519864760
|View full text |Cite
|
Sign up to set email alerts
|

Task-oriented Motor Learning in Upper Extremity Rehabilitation Post Stroke

Abstract: Background: Upper extremity deficits are the most popular symptoms following stroke. Task-oriented training has the ability to increase motor area excitability in the brain, which can stimulate the recovery of motor control. Objective: This study was aimed to examine the efficiency of the task-oriented approach on paretic upper extremity following a stroke, and to identify efficient treatment dosage in those populations. Method: We searched through PubMed, Scopus, Physiotherapy Evidence Database (PEDro), Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…50 The tDCS may lower the threshold of these physiological changes following training, and then the tDCS could improve this plasticity and increase duration of the effect. 50 Recently, many rehabilitation interventions have demonstrated effectiveness on spasticity in patients with various neurological disorders, such as mental practice, 51 focal muscle vibration, 16,20 FES, 52 task-oriented, 53 and whole-body vibration. 19 Thus, this systematic review indicated that combining tDCS with one of these interventions at the same time might show a significant reduction in spasticity post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…50 The tDCS may lower the threshold of these physiological changes following training, and then the tDCS could improve this plasticity and increase duration of the effect. 50 Recently, many rehabilitation interventions have demonstrated effectiveness on spasticity in patients with various neurological disorders, such as mental practice, 51 focal muscle vibration, 16,20 FES, 52 task-oriented, 53 and whole-body vibration. 19 Thus, this systematic review indicated that combining tDCS with one of these interventions at the same time might show a significant reduction in spasticity post-stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the cognitive function aspect of limb apraxia rehabilitation, recently, many rehabilitation interventions were found to be effective in improving cognitive functions through stimulating neuroplasticity, such as virtual reality . Moreover, in terms of the motor function aspect of limb apraxia rehabilitation, various rehabilitation interventions showed their effects on the motor function, such as focal muscle vibration Annino et al, 2019), task-oriented interventions (Alashram et al, 2019a), and rhythmic auditory stimulation (Alashram et al, 2019b). Hence, combining these interventions with existing limb apraxia interventions (i.e., strategy training, gesture training) in future studies may show superior benefits than using strategy training or gesture training alone.…”
Section: Discussionmentioning
confidence: 99%
“…It used to improve physical impairments and maximize functional performance abilities. 8 There were some limitations to this CARE. The VO 2 max may provide an accurate examination of energy expenditure in perfect sittings; however, in physiotherapy gym sittings, the use of VO 2 max may not be a feasible choice and other measures, such as 6-MWT with a portable metabolic system, may include in future studies.…”
Section: Discussionmentioning
confidence: 99%